2018
DOI: 10.1007/s12551-018-0445-0
|View full text |Cite
|
Sign up to set email alerts
|

Cofilin and profilin: partners in cancer aggressiveness

Abstract: This review covers aspects of cofilin and profilin regulations and their influence on actin polymerisation responsible for cell motility and metastasis. The regulation of their activity by phosphorylation and nitration, miRs, PI(4,5)P binding, pH, oxidative stress and post-translational modification is described. In this review, we have highlighted selected similarities, complementarities and differences between the two proteins and how their interplay affects actin filament dynamics.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
27
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(35 citation statements)
references
References 154 publications
(187 reference statements)
6
27
0
1
Order By: Relevance
“…Additionally, we observed that NRP2 enriched co lin in the detergentinsoluble fraction ( Figure 3G(a)). Co lin regulation and its effects on actin polymerization are responsible for cell motility and metastasis [31]. Indeed, according to our data, NRP2 promoted co lin activity in PNET-associated HUVECs, which resulted in increased actin polymerization, membrane protrusion, and cell migration.…”
Section: Discussionsupporting
confidence: 63%
“…Additionally, we observed that NRP2 enriched co lin in the detergentinsoluble fraction ( Figure 3G(a)). Co lin regulation and its effects on actin polymerization are responsible for cell motility and metastasis [31]. Indeed, according to our data, NRP2 promoted co lin activity in PNET-associated HUVECs, which resulted in increased actin polymerization, membrane protrusion, and cell migration.…”
Section: Discussionsupporting
confidence: 63%
“…3 G(a)). Cofilin regulation and its effects on actin polymerization are responsible for cell motility and metastasis [ 31 ]. Indeed, according to our data, NRP2 promoted cofilin activity in PNET-associated HUVECs, which resulted in increased actin polymerization, membrane protrusion, and cell migration.…”
Section: Discussionmentioning
confidence: 99%
“…We also measured an increase in PKCζ/λ (T410/T4033) and cofilin (S3) phosphorylation at the 2-day time point with both single and combined kinase inhibition ( Figure S5). Cofilin is an actin depolymerizing factor known to regulate actin dynamics and cell invasion; however, recent studies have established the role of cofilin in NFκB nuclear translocation [31,32]. The atypical protein kinase C member PKCζ is involved in several survival pathways that are deregulated in cancer and is also involved in the activation of NFκB [33,34].…”
Section: Kinome Response To Combined Met and Mek Inhibition In Nf1-rementioning
confidence: 99%